COMP: A Potential Early Biomarker of RAS After Lung Transplantation. Issue 8 (19th July 2021) - Novo, Mirza; Westin, Johan; Andersson, Lars-Magnus; Jonsson Berdenius, Anton; Nordén, Rickard; Magnusson, Jesper M.
Abstract : Background: Chronic rejection, defined as chronic lung allograft dysfunction (CLAD), is the major factor limiting long-term survival after lung transplantation (LTx). A specific subgroup of CLAD is restrictive allograft syndrome (RAS). CLAD's pathogenesis is largely unknown, but previous findings suggest that it is associated with increased fibrosis in the transplanted lung. Cartilage oligomeric matrix protein (COMP) has been associated with multiple fibrotic conditions. The current study aimed to explore the relation between COMP serum levels and development of CLAD, and RAS in particular, in a retrospective cohort of LTx patients. Methods: This study included retrospective data from patients who underwent LTx during 2009–2011. Blood samples and spirometry data were obtained at follow-up visits 1, 3, 6, 9, and 12 mo after transplantation. Serum samples were analyzed for COMP. CLAD and RAS were defined according to the 2019 International Society for Heart and Lung Transplantation consensus document. Results: Data from 38 patients (19 men and women, respectively) were collected. Twenty-three patients (60.5%) developed CLAD, of whom 6 (26.1 %) fulfilled the criteria for RAS. Patients who developed RAS had higher mean COMP levels between 1 and 3 mo after LTx than those who did not develop RAS (10.9 [3.9-17.5] U/L vs 7.4 [3.9-10.8] U/L, P  = 0.008). RAS was also associated with shorter survival. We found no association between COMP levels and CLAD of other types than RAS. Conclusions: Serum level of COMP early after LTx seems to be associated with RAS development and might serve as a biomarker suitable for clinical use in the LTx setting. Abstract :